2015
DOI: 10.2174/1567202612666150819100746
|View full text |Cite
|
Sign up to set email alerts
|

Normobaric Hyperoxia Preconditioning Induces Changes in the Brain Lipidome

Abstract: Recent investigations have demonstrated that normobaric hyperoxia induces neuroprotection against ischemic injury. The aim of study was to determine the survey of HO (hyperoxia) preconditioning on brain lipidome.The animals were assigned into three groups, the first experimental group was exposed to 95% inspired HO for 4 h /day for six consecutive days. The second experimental group considered as the control group and was exposed to 21% oxygen as room air (RA) in the same chamber. The third group acted as sham… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It is well-established that Cer is involved in oxidative stress, inflammation, and/or cell death, which contribute to the development of AD. Apoptosis is stimulated by Cer though the inhibition of mitochondrial electron transport and cytochrome release (Faezi et al, 2015). High levels of Cer in the brain can promote inflammatory pathways and exert negative effects on neurons during the aging process (Cutler et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It is well-established that Cer is involved in oxidative stress, inflammation, and/or cell death, which contribute to the development of AD. Apoptosis is stimulated by Cer though the inhibition of mitochondrial electron transport and cytochrome release (Faezi et al, 2015). High levels of Cer in the brain can promote inflammatory pathways and exert negative effects on neurons during the aging process (Cutler et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it has been shown that hyperoxia preconditioning significantly decreased the brain LPC levels and ischemic brain injury (27), suggesting an important association of LPC content with brain injury. Excessive conversion of PC to LPC appears to be detrimental to the brain recovering from cerebral ischemia.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the Rf value is not sufficient for the detection of compounds on the TLC plate; as a result, each spot was picked up from the plate and the predicted targets of compounds were investigated using offline mass spectrometry. The molecular weight of various lipids in the rat brain samples is shown in our previous study (19).…”
Section: Esi/it Mass Spectrometrymentioning
confidence: 80%